The Role of Artificial Intelligence in Shaping Digital Media Consumption - Majid Ali Shah; Zaiba Azeem; Faisal Saleem; Ghulam Sarwar (Inverge Journal of Social Sciences, 2025)
The widespread application of Artificial Intelligence (AI) to digital media spaces altered both the quality of the content curation and personalization and the interaction between users and the content. One should know how it affects the consumption patterns, user awareness, and user perceptions to navigate the evolving world of digital. The purpose of this study is to empirically examine how AI affects the formation of digital media consumption with several objectives to determine the awareness of users, the behavioural impact, perceptions and concerns, and the overall effect on convenience and dependency. Quantitative research design was used, and a structured online survey was used among a sample of 320 users of digital media. Data analysis was done using the descriptive statistics as a means of summarizing demographic features and important variables and the results were presented graphically using bar charts. The results show that the awareness of users regarding the application of AI is high as 78.1% of the participants acknowledge the usage of AI in platforms. AI has a huge effect on behaviour with 71.9% indicating that it had more time on media because of recommendations and 72.5% indicating that it had an impact on their entertainment decisions. Although three out of four (79.1) were in agreement with the idea of AI making things more convenient and enhancing the experience, there have been serious questions about privacy (64%), diversity of content (63.2%), and the bias of the algorithm (64.1%). A resounding majority (79.1) demanded increased openness in the activities of AI. AI is a revolutionary impact in digital media increasing personalization and user satisfaction, at the same time creating dependency and ethical issues. The paper concludes that an ethically transparent, user-centric, and digitally literate comprehensive approach is necessary when integrating AI into future digital ecosystems. References Afshar, M. Z., & Shah, M. H. (2025). Leveraging Porter's diamond model: Public sector insights. The Critical Review of Social Sciences Studies, 3(2), 2255–2271. Afzal, M., Arshad, N., & Shaheen, A. (2025). ChatGPT and the future of academic writing: Enhancing productivity and creativity. Journal of Engineering and Computational Intelligence Review, 3(1), 1–11. Alzub, A. M. (2023). Navigating the disruption of digital and conventional media in changing media consumption landscape in digital era. Journal of Engineering, Technology, and Applied Science (JETAS), 5(1), 38–48. Asif, M., & Asghar, R. J. (2025). Managerial accounting as a driver of financial performance and sustainability in small and medium enterprises in Pakistan. Center for Management Science Research, 3(7), 150-163. https://doi.org/10.5281/zenodo.17596478 Asif, M., & Sandhu, M. S. (2023). Social media marketing revolution in Pakistan: A study of its adoption and impact on business performance. Journal of Business Insight and Innovation, 2(2), 67-77. Asif, M., Shah, H., & Asim, H. A. H. (2025). Cybersecurity and audit resilience in digital finance: Global insights and the Pakistani context. Journal of Asian Development Studies, 14(3), 560-573. https://doi.org/10.62345/jads.2025.14.3.47 Bag, S., Srivastava, G., Bashir, M. M. A., Kumari, S., Giannakis, M., & Chowdhury, A. H. (2022). Journey of customers in this digital era: Understanding the role of artificial intelligence technologies in user engagement and conversion. Benchmarking: An International Journal, 29(7), 2074–2098. https://doi.org/10.1108/BIJ-05-2021-0275 Bradshaw, S., & Howard, P. N. (2018). Challenging truth and trust: A global inventory of organized social media manipulation. The Computational Propaganda Project, 1, 1–26. Broussard, M., Diakopoulos, N., Guzman, A. L., Abebe, R., Dupagne, M., & Chuan, C. H. (2019). Artificial intelligence and journalism. Journalism & Mass Communication Quarterly, 96(3), 673–695. https://doi.org/10.1177/1077699019836460 Brundage, M., Avin, S., Clark, J., Toner, H., Eckersley, P., Garfinkel, B., ... & Amodei, D. (2018). The malicious use of artificial intelligence: Forecasting, prevention, and mitigation. arXiv preprint arXiv:1802.07228. Cai, J. (2021, July). Artificial intelligence in digital media technology. In International Conference on Frontier Computing (pp. 188–195). Springer Nature Singapore. Chen, C. (2022). Study on the innovative development of digital media art in the context of artificial intelligence. Computational Intelligence and Neuroscience, 2022, Article 1004204. https://doi.org/10.1155/2022/1004204 Criado, J. I., & Gil-Garcia, J. R. (2019). Creating public value through smart technologies and strategies: From digital services to artificial intelligence and beyond. International Journal of Public Sector Management, 32(5), 438–450. https://doi.org/10.1108/IJPSM-01-2018-0006 Grover, P., Kar, A. K., & Dwivedi, Y. K. (2022). Understanding artificial intelligence adoption in operations management: Insights from the review of academic literature and social media discussions. Annals of Operations Research, 308(1), 177–213. https://doi.org/10.1007/s10479-021-04200-3 Kumar, V., Rajan, B., Venkatesan, R., & Lecinski, J. (2019). Understanding the role of artificial intelligence in personalized engagement marketing. California Management Review, 61(4), 135–155. https://doi.org/10.1177/0008125619867911 Lee, J., Suh, T., Roy, D., & Baucus, M. (2019). Emerging technology and business model innovation: The case of artificial intelligence. Journal of Open Innovation: Technology, Market, and Complexity, 5(3), 44. https://doi.org/10.3390/joitmc5030044 Lim, J. S., & Zhang, J. (2022). Adoption of AI-driven personalization in digital news platforms: An integrative model of technology acceptance and perceived contingency. Technology in Society, 69, 101965. https://doi.org/10.1016/j.techsoc.2022.101965 Lim, J. S., Shin, D., Zhang, J., Masiclat, S., Luttrell, R., & Kinsey, D. (2023). News audiences in the age of artificial intelligence: Perceptions and behaviors of optimizers, mainstreamers, and skeptics. Journal of Broadcasting & Electronic Media, 67(3), 353–375. https://doi.org/10.1080/08838151.2023.2189103 Lutz, C. (2019). Digital inequalities in the age of artificial intelligence and big data. Human Behavior and Emerging Technologies, 1(2), 141–148. https://doi.org/10.1002/hbe2.115 Makki, A., & Jawad, O. (2023). Future challenges in receiving media messages in light of developments in artificial intelligence. Migration Letters: An International Journal of Migration Studies, 20, 167–183. Nama, N. P. (2021). Enhancing user experience in mobile applications through AI-driven personalization and adaptive learning algorithms. World Journal of Advanced Engineering Technology and Sciences, 3(2), 83–94. Nassar, S. (2024). AI and algorithms tackling the media and creative industries: Addressing societal consumer behavior directions and challenges in the next digital frontier. Arab Media & Society, (37). Nasser El Erafy, A. (2023). Applications of artificial intelligence in the field of media. International Journal of Artificial Intelligence and Emerging Technology, 6(2), 19–41. Nwanna, M., Offiong, E., Ogidan, T., Fagbohun, O., Ifaturoti, A., & Fasogbon, O. (2025). AI-driven personalisation: Transforming user experience across mobile applications. Journal of Artificial Intelligence, Machine Learning and Data Science, 3(1), 1930–1937. Prakash, G., & Sabharwal, D. (2024). AI revolution in online media: Transforming content creation, distribution, and consumption. Media and AI: Navigating, 179. Risteska, A. (2023). Aware and critical navigation in the media landscape: (Un)biased algorithms and the need for new media literacy in the era of artificial intelligence and digital media. KAIROS: Media and Communications Review, 2(2), 16–38. Salma, B., Fatima, T., Sara, A., & Merieme, B. (2024, April). Artificial intelligence in social media: From content personalization to user engagement. In The International Workshop on Big Data and Business Intelligence (pp. 45–52). Springer Nature Switzerland. Shin, D., Hameleers, M., Park, Y. J., Kim, J. N., Trielli, D., Diakopoulos, N., ... & Baumann, S. (2022). Countering algorithmic bias and disinformation and effectively harnessing the power of AI in media. Journalism & Mass Communication Quarterly, 99(4), 887–907. https://doi.org/10.1177/10776990221095460 Ullah, A., Islam, K., Ali, A., & Baber, M. (2024). Assessing the impact of social media addiction on reading patterns: A study of Riphah International University students. International Journal of Human and Society, 4(1), 1250–1262. Walia, R., & Jain, K. (2023). Algorithmic alchemy: The transformative power of AI in shaping media narratives. International Journal for Multidimensional Research Perspectives, 1(3), 239–247. Wang, S. (2023). Factors related to user perceptions of artificial intelligence (AI)-based content moderation on social media. Computers in Human Behavior, 149, 107971. https://doi.org/10.1016/j.chb.2023.107971 Zaka, S., Latif, A., Ali, A., & Ahmad, H. M. (2023). The impact of social media addiction on exacerbating loneliness among youth. Bulletin of Business and Economics (BBE), 12(4), 419–424. Zhai, Y., Yan, J., Zhang, H., & Lu, W. (2020). Tracing the evolution of AI: Conceptualization of artificial intelligence in mass media discourse. Information Discovery and Delivery, 48(3), 137–149.